Cities and Energy Consumption: a Critical Review - Gargiulo, Carmela; Russo, Laura (TeMA - Journal of Land Use, Mobility and Environment, 2017)
The relationship between cities and energy consumption has been of great interest for the scientific community for over twenty years. Most of the energy consumption, indeed, occurs in cities because of the high concentration of human activities. Thus, cities are responsible for a big share of carbon dioxide emissions (CO2). However, the debate on this topic is still open, mainly because of the heterogeneity of published studies in the selection, definition and measurement of the urban features influencing energy consumption and CO2 emissions, as well as in the choice of the energy sectors to be considered, in the territorial scale of analysis, and in the geographical distribution of the sample. Therefore, the goal of this research is to systematize and compare the approach, methodology and results of the relevant literature on the relationship between cities and energy consumption over the last twenty years. Furthermore, this critical review identifies the knowledge gap between what is known and what is still under debate and, based on that, it proposes a conceptual framework that will help to outline a new direction for future research and support local policy makers in the definition of strategies and actions that can effectively reduce urban energy use and CO2 emissions.